Gut epithelial barrier dysfunction in lupus triggers a differential humoral response against gut commensals - Botía-Sánchez, María; Galicia, Georgina; Albaladejo-Marico, Lorena; Toro-Domínguez, Daniel; Morell, Maria; Marcos-Fernández, Raquel; Margolles, Abelardo; Alarcón-Riquelme, Marta E. (Frontiers in Immunology, 2023)
Introduction Systemic lupus erythematosus is an autoimmune disease with multisystemic involvement including intestinal inflammation. Lupus-associated intestinal inflammation may alter the mucosal barrier where millions of commensals have a dynamic and selective interaction with the host immune system. Here, we investigated the consequences of the intestinal inflammation in a TLR7-mediated lupus model. Methods IgA humoral and cellular response in the gut was measured. The barrier function of the gut epithelial layer was characterised. Also, microbiota composition in the fecal matter was analysed as well as the systemic humoral response to differential commensals. Results The lupus-associated intestinal inflammation modifies the IgA+ B cell response in the gut-associated lymphoid tissue in association with dysbiosis. Intestinal inflammation alters the tight junction protein distribution in the epithelial barrier, which correlated with increased permeability of the intestinal barrier and changes in the microbiota composition. This permeability resulted in a differential humoral response against intestinal commensals. Discussion Lupus development can cause alterations in microbiota composition, allowing specific species to colonize only the lupus gut. Eventually, these alterations and the changes in gut permeability induced by intestinal inflammation could lead to bacterial translocation.